2018
DOI: 10.18332/tpc/90411
|View full text |Cite
|
Sign up to set email alerts
|

Maternal smoking during pregnancy in Greece

Abstract: is an open access, peer-reviewed online journal that encompasses all aspects of tobacco use, prevention and cessation that can promote a tobacco free society. The aim of the journal is to foster, promote and disseminate research involving tobacco use, prevention, policy implementation at a regional, national or international level, disease development-progression related to tobacco use, tobacco use impact from the cellular to the international level and finally the treatment of tobacco attributable disease thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…7 A study conducted in a public maternity hospital in Athens, Greece reports that 24.6% of pregnant women continued to smoke during pregnancy. 8 Tobacco addiction is a chronic disease influenced by a number of complex factors such as the central nervous system, genetics, the environment, and physical and psychological states. 9 Both active and second-hand smoking (SHS) can cause complications during pregnancy and after delivery, such as placental abruption, placenta…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 A study conducted in a public maternity hospital in Athens, Greece reports that 24.6% of pregnant women continued to smoke during pregnancy. 8 Tobacco addiction is a chronic disease influenced by a number of complex factors such as the central nervous system, genetics, the environment, and physical and psychological states. 9 Both active and second-hand smoking (SHS) can cause complications during pregnancy and after delivery, such as placental abruption, placenta…”
Section: Introductionmentioning
confidence: 99%
“…Another study in USA found that 7.1% of women reported smoking during pregnancy, at both high and low intensity, with higher smoking rates in the first trimester 7 . A study conducted in a public maternity hospital in Athens, Greece reports that 24.6% of pregnant women continued to smoke during pregnancy 8 …”
Section: Introductionmentioning
confidence: 99%